A JOURNEY WITHOUT A MAP: CHALLENGES AND STRATEGIES FOR INDIE MUSIC TO CROSS NATIONAL MARKETS - Aryandari, Citra; Hendrawan, Danu (Institut Seni Indonesia (ISI) Surakarta, 2024)
Indie or independent music is created and distributed independently without the intervention of major record labels. The development of the internet and digital platforms provides opportunities for indie musicians to disseminate their work, but they still face difficulties in distribution and promotion to penetrate the national music market. This research aims to identify the barriers to digital distribution and promotion faced by local indie bands and find effective digital distribution and promotion strategies to penetrate the national market. The method used is in-depth interviews with indie musicians, independent label owners, music aggregators, and support staff involved in digital distribution. Qualitative data from the interviews will be analyzed to find themes, answer patterns, and explain respondents' perspectives comprehensively. The results of this research are expected to provide an in-depth understanding of the distribution and promotion problems faced by indie bands and formulate solutions in the form of appropriate strategies to expand their market reach to the national level and increase their visibility and popularity.